Breeding onion for resistance to Fusarium basal rot: comparison of field selection and artificial inoculation - Caligiore Gei, Pablo Fernando (2020)
Fusarium basal rot (FBR) is one of the main onion diseases in Argentina. The Onion Breeding National Program, held at INTA Experimental Station in La Consulta, Argentina, has developed onion breeding lines with increased resistance to FBR through a selection scheme performed under field conditions. The aim of the present work was to evaluate the achieved response to selection in the FBR resistance trait, comparing two strategies: selection under field environment and artificial inoculations performed in controlled conditions. Seeds of the breeding line 17-1289 (P0) were inoculated with Fusarium oxysporum f.sp. cepae (isolate FOC LJC10081), one seed per cap. After 15 days 162 surviving plants were treated with fungicide and transplanted. The resulting bulbs were planted and recombined avoiding contamination with foreign pollinators. The obtained seeds were labelled as PCC (Progeny generated under Controlled Conditions). Another portion of P0 seeds was grown under field conditions in a FBR-conductive soil. The best bulbs were selected at harvest based on their FBR resistance score, root system quality and agronomic features. These bulbs later produced seeds by recombination in isolation and were labelled as PFC (Progeny generated under Field Conditions). The P0 population and the PCC-PFC progenies were then compared through a standardized test for determination of FBR resistance, using two inoculum concentrations in the substrate. The incidence of FBR was significantly reduced in PCC at high inoculum concentrations, in comparison to the original population P0. Disease progression was delayed and lower rates were achieved in PCC. The described lab selection technique may constitute an interesting and useful tool to select materials that carry genetic resistance and contribute to an integrative approach, complemented with selection under field conditions, in onion breeding programs for FBR resistance.